A Phase 1 Dose‐Escalation Study of Low‐Dose Metronomic Treatment With Novel Oral Paclitaxel Formulations in Combination With Ritonavir in Patients With Advanced Solid Tumors. Issue 6 (5th October 2020) - de Weger, Vincent A.; Vermunt, Marit A.C.; Stuurman, Frederik E.; Burylo, Artur M.; Damoiseaux, David; Hendrikx, Jeroen J.M.A.; Sawicki, Emilia; Moes, Johannes J.; Huitema, Alwin D.R.; Nuijen, Bastiaan; Rosing, Hilde; Mergui‐Roelvink, Marja; et al.
Abstract: ModraPac001 (MP1) and ModraPac005 (MP5) are novel oral paclitaxel formulations that are coadministered with the cytochrome P450 3A4 inhibitor ritonavir (r), enabling daily low‐dose metronomic (LDM) treatment. The primary aim of this study was to determine the safety, pharmacokinetics and maximum tolerated dose (MTD) of MP1/r and MP5/r. The second aim was to establish the recommended phase 2 dose (RP2D) as LDM treatment. This was an open‐label phase 1 trial. Patients with advanced solid tumors were enrolled according to a classical 3+3 design. After initial employment of the MP1 capsule, the MP5 tablet was introduced. Safety was assessed using the Common Terminology Criteria for Adverse Events version 4.02. Pharmacokinetic sampling was performed on days 1, 2, 8, and 22 for determination of paclitaxel and ritonavir plasma concentrations. In this study, 37 patients were treated with up to twice‐daily 30‐mg paclitaxel combined with twice‐daily 100‐mg ritonavir (MP5/r 30‐30/100‐100) in 9 dose levels. Dose‐limiting toxicities were nausea, (febrile) neutropenia, dehydration and vomiting. At the MTD/RP2D of MP5/r 20‐20/100‐100, the maximum paclitaxel plasma concentration and area under the concentration‐time curve until 24 hours were 34.6 ng/mL (coefficient of variation, 79%) and 255 ng h/mL (coefficient of variation, 62%), respectively. Stable disease was observed as best response in 15 of 31 evaluable patients. Based on these results, LDM therapy with oral paclitaxel coadministrated with ritonavir was considered feasible and safe. The MTD and RP2D were determined as MP5/r 20‐20/100‐100. Further clinical development of MP5/r as an LDM concept, including potential combination treatment, is warranted.